KUALITAS APARATUR DESA DALAM MENINGKATKAN KINERJA PEMERINTAHAN DESA: (Bukti dari Desa Tanjungjaya, Kabupaten Bandung Barat, Indonesia) - Radiansyah, Rifi Rivani; Nugraha, Wildan (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
This study aims to analyze the quality of village government apparatus in supporting the performance of the Tanjungjaya Village Government, Cihampelas Subdistrict, West Bandung Regency. The analysis is grounded in a theoretical framework of apparatus quality encompassing human resource quality, service quality, and performance quality. This research adopts a qualitative method with an inductive descriptive approach. Data were collected through in-depth interviews with village officials and community members, direct observation of public service practices, and analysis of official village documents. Unlike previous studies, this research explicitly links apparatus quality to the stagnation of the Village Development Index (IDM) status of Tanjungjaya Village during the 2020–2024 period. The novelty of this study lies in identifying a gap between relatively adequate formal educational qualifications of village officials and suboptimal public service performance. This finding contributes to the literature by emphasizing that formal education alone is insufficient to ensure effective village governance without technical competence, work discipline, and professional service orientation. The results indicate that apparatus quality is moderately satisfactory, reflected in administrative knowledge, work experience, service reliability, and responsiveness to community needs. However, limited personnel capacity, inadequate infrastructure, and weak adaptation to digital-based public services remain significant constraints. Therefore, strengthening apparatus capacity through applied technical training, service innovation, and performance-based governance is essential to accelerate improvements in village development status as measured by the IDM.